The School Meals System in the Region: Sources of Funding, Organization, and Infrastructure - Natalya STAROVOYTOVA; Natalya ALEKSANDROVA; Viktor STUKACH (Communications of International Proceedings, 2021)
The paper considers the state of the nutrition system of students in schools of the Omsk region. The sources of funding in the school nutrition system, the quality of student services, the practice of competitive selection of service providers and the purchase of raw materials, the cost of food products, the material and technical base of schools, and the qualifications of staff are studied. Problems in the organization of food in schools of the Omsk region are identified and classified. The study revealed negative practices. The essence of one of them is that a significant part of the institutions that have signed a contract for the supply of food with a single supplier do not have a choice, they are forced to purchase at the prices offered by the supplier. The goal is to form the organizational, economic and social foundations of the "School Meals" system in the region, as the main instrument of domestic food aid. Propose measures to provide the system with sources of financing, effective work of state and municipal regulatory organizations, the creation of infrastructure links that ensure the interaction of consumers and suppliers in the market system, the creation of a mechanism for quality control and sanitary conditions, the organization of food supplies, primarily domestic production with the necessary level of quality.
Keywords: School Nutrition System; Infrastructure; Institutional Environment